Green Synthesis of Nanoscale Zero-Valent Iron and Its Activity as an Adsorbent for Ni(II) and Cr(VI) - Novia Apriliani (Chemistry and Materials, 2022)
Zero-valent iron nanoparticles (nZVI) were successfully synthesized by metal salt reduction method using cinnamon as a reductor agent. Particle size analysis showed that the most optimum composition of FeSO4 and polyphenols was at a ratio of 4:1, resulting in Dv(10), Dv(50), and Dv(90) values of 23.7 nm, 44.6 nm, and 178 nm, respectively. Scanning electron microscopy showed that nZVI was spherical and agglomerated. X-ray diffraction pattern showed a peak at  45.03˚  that corresponds to nZVI. The batch test showed that nZVI has Ni(II) and Cr(VI) adsorption activity of 95.58% Ni and 64.29%, respectively.